A High‐Potential Anion‐Insertion Carbon Cathode for Aqueous Zinc Dual‐Ion Battery. (12th July 2020) - Guo, Qiubo; Kim, Keun‐il; Jiang, Heng; Zhang, Lu; Zhang, Chong; Yu, Dongxu; Ni, Qiao; Chang, Xiaoqing; Chen, Tingting; Xia, Hui; Ji, Xiulei
Abstract: Aqueous dual‐ion batteries (DIBs) are promising for large‐scale energy storage due to low cost and inherent safety. However, DIBs are limited by low capacity and poor cycling of cathode materials and the challenge of electrolyte decomposition. In this study, a new cathode material of nitrogen‐doped microcrystalline graphene‐like carbon is investigated in a water‐in‐salt electrolyte of 30 m ZnCl2, where this carbon cathode stores anions reversibly via both electrical double layer adsorption and ion insertion. The (de)insertion of anions in carbon lattice delivers a high‐potential plateau at 1.85 V versus Zn 2+ /Zn, contributing nearly 1/3 of the capacity of 134 mAh g −1 and half of the stored energy. This study shows that both the unique carbon structure and concentrated ZnCl2 electrolyte play critical roles in allowing anion storage in carbon cathode for this aqueous DIB. Abstract : The nitrogen‐doped few‐layered graphene cathode exhibits a high reversible capacity of 134 mAh g −1 . Therein, 40 mAh g −1 comes from the [ZnCl x ] 2− x (de)insertion plateaus at 1.85/1.95 V versus Zn 2+ /Zn, the rest originates from electrical double layer capacitance. Characterization reveals that [ZnCl x ] 2− x ions are reversibly inserted into the graphenic structures, whereas the chloride insertion in the first cycle is irreversible.